Methodology for vegetation inventory and grazing capacity assessment. - Sibanda, H. M.; Venema, J. H.; Magama, P.; Dzadya, W.; Masaka, Johnson; Makaza, E. (United Nations Development Programme (UNDP). Food and Agriculture Organization of the United Nations, 2021)
Methodology for vegetation inventory and grazing capacity assessment. Based on the work of H.M. Sibanda, J.H. Venema, P. Magama, W. Dzadya, J. Masaka, E. Mazaka.